Strategi Program Pemberdayaan Desa Dalam Mengembangkan Ekonomi Masyarakat di Dusun Cappakala Kabupaten Pinrang (Perspektif Maqashid Syariah) - Nurul Mutmainna; Mustamin B; Wahyuni (Mappideceng:Jurnal Ekonomi Syariah, 2024)
This study aims to analyze the Village Empowerment Program Strategy in Developing the Community Economy in Cappakala Hamlet, Pinrang Regency based on the Maqāṣid Sharīʿah perspective. The background of this study is the government's efforts through the establishment of Village-Owned Enterprises (BUMDes) to explore village potential and improve welfare, as mandated in Law No. 32 of 2004 and Government Regulation No. 43 of 2014. Cappakala Hamlet has local potential that needs to be managed synergistically by the village government and the community to encourage economic growth. This study uses a descriptive qualitative approach. Primary data sources were obtained through in-depth interviews with the Village Head, Village Secretary, and the community of Cappakala Hamlet. Secondary data were obtained from archives, books, and journals related to community empowerment, economic development, and Maqāṣid Sharīʿah. Data analysis was carried out through data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the village empowerment program strategy in Cappakala Hamlet seeks to establish BUMDes with business units such as BRI Link, sewing groups, and savings and loans. This strategy was developed by integrating the principles of Maqāṣid Sharīʿah (maintenance of religion/din, soul/nafs, reason/‘aql, descendants/nasl, and wealth/māl). The implementation of the Maqāṣid Sharīʿah perspective is realized through: (a) Sustainable Economic Empowerment (Property) through sharia-based MSMEs; (b) Increasing Access to Education and Skills (Intellect) through technical training; (c) Increasing Social and Health Welfare (Soul); (d) Maintaining Religion and Spirituality (Religion) through worship development and access to sharia banking; and (e) Developing Supporting Infrastructure (Descendants). Overall, this strategy is aimed at creating comprehensive, sustainable community welfare in accordance with Islamic values.